2022
DOI: 10.21037/atm-22-5668
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective diagnostic test study on circulating tumor cells and artificial intelligence imaging in patients with lung adenocarcinoma

Abstract: Background: Either tumor volume or folate-receptor-positive circulating tumor cells (FR + CTC) has been proven effective in predicting tumor cell invasion. However, it has yet to be documented to use FR + CTC along with artificial intelligence (AI) tumor volume to differentiate between pathological subtypes of lung adenocarcinoma (LUAD). Therefore, this study is aimed to evaluate the accuracy of FR + CTC and AI tumor volume for classifying the invasiveness of LUAD. Methods: A total of 226 patients who were dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Several recent studies have reported that the combination of CTCs and additional dimensional features (e.g., nodules radiological size, serum tumor marker) could significantly improve the differentiation ability of small lung nodules with high sensitivity and specificity ( 13 , 17 , 19 ). Besides, the combination of CTCs and artificial intelligence imaging was also shown to be an independent indicator for lung adenocarcinoma invasiveness in our previously published study ( 20 ). However, compared with traditional radiological features, radiomics has been shown to be a more effective clinical application tool for differentiating lung nodules in the early screening for lung cancer ( 21 ), since it can quickly extract a larger number of quantitative features from radiological images using high-throughput calculations ( 22 - 24 ).…”
Section: Introductionmentioning
confidence: 58%
“…Several recent studies have reported that the combination of CTCs and additional dimensional features (e.g., nodules radiological size, serum tumor marker) could significantly improve the differentiation ability of small lung nodules with high sensitivity and specificity ( 13 , 17 , 19 ). Besides, the combination of CTCs and artificial intelligence imaging was also shown to be an independent indicator for lung adenocarcinoma invasiveness in our previously published study ( 20 ). However, compared with traditional radiological features, radiomics has been shown to be a more effective clinical application tool for differentiating lung nodules in the early screening for lung cancer ( 21 ), since it can quickly extract a larger number of quantitative features from radiological images using high-throughput calculations ( 22 - 24 ).…”
Section: Introductionmentioning
confidence: 58%
“…Based on these past experiences, an attempt was made to combine the number of FR + CTCs with the AI-assisted diagnosis tumor volume system (ScrynPro) to predict lung cancers with different invasive abilities. After the analysis, compared with using FR + CTCs and tumor volume alone, the combination of the two can be used to predict the invasion ability of lung cancer more accurately (AUC = 0.841) [153].…”
Section: Othersmentioning
confidence: 99%
“…In medical image proce ssing, DL techniques have advantages such as high accuracy and strong adapta bility. In recent years, with the rapid development of DL technology, an increa sing number of scholars have harnessed it for medical domain, and great stride s have been made [21][22][23] . However,there are relatively few studies on the constr uction of lung adenocarcinoma data set and intelligent detection,which conflict s with the urgent treatment needs.…”
Section: Introductionmentioning
confidence: 99%